Web-based industrial training assessment using open source service / Norlina M. Ali … [et al.] - M. Ali, Norlina; Mohd Rick, Abd. Malik; A. Latif, Ruziah; Noh, Mohd Khairul Ariff; Zaharum, Zaibedah; Shahwir, Siti Farrah; Md Isa, Mohamad Azwan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Industrial training is the final course in the Degree Program, where a student is expected to undergo on the job training in area relevant to the field of specialization. This training is to be conducted to the selection host organizations in accordance to the industrial training guidelines. The students will be assessed and graded based on internship performance. The facilitator of host organizations contribute 60% of the final score and 40% is assessed by respective advisors in the faculty. Looking at the mutual relationship between advisors and facilitator of host organizations, there is a need for the development of a new automated system using web based concepts for creation of effective and efficient coordination and monitoring of student performance. This web based system can simply the flow of evaluation process. This can be achieved by easing the authentication process. Furthermore, there is no cost involve in developing and maintaining of IT infrastructures for the deployment of this system since we are adopting the open source service. With the new platform, it is hoped that we are able to integrate UiTM industrial training system through efficiency in coordinating and controlling of student industrial training performances.